Relative quantification of human β‐defensins by a proteomics approach based on selected reaction monitoring. (10th August 2015) - Kalló, Gergő; Chatterjee, Arunima; Tóth, Márta; Rajnavölgyi, Éva; Csutak, Adrienne; Tőzsér, József; Csősz, Éva
Abstract : Rationale: A targeted proteomics method based on selected reaction monitoring (SRM) is a relevant approach for the analysis of multiple analytes in biological samples. Defensins are phylogenetically conserved small antimicrobial peptides contributing to innate host defense and exhibiting low immunogenicity, resistance to proteolysis and a broad range of antimicrobial activities. The goal of the present study was to develop and optimize SRM‐based targeted proteomics methods for the detection of human β‐defensins 1–4 in various biological fluids. Methods: An SRM‐based targeted proteomics method was developed and validated for the detection of human β‐defensins 1–4. The supernatants of resting and IL‐1β‐stimulated Caco2, HT‐29 and SW‐1116 colonic epithelial cells (CEC), cell lysates of CECs and tear samples of human healthy individuals were analyzed and the feasibility of the developed method was validated by ELISA and dot‐blot analysis complemented by RT‐qPCR. Results: Our results demonstrate that the developed SRM method offers an alternative approach for the cost‐effective and rapid analysis of human β‐defensins in samples with biological relevance. Conclusions: A semi‐quantitative targeted mass spectrometry method was developed and validated for the relative quantification of β‐defensins 1–4 in cell culture supernatants and body fluid analyses. Copyright © 2015 John Wiley & Sons, Ltd.